1-methylcyclopropeneand storage temperature effect in postharvest of mandarin (Citrus reticulata L.) var. Arrayana - Gómez, Carlos A.; Herrera, Aníbal O.; Flórez, Víctor J. (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2015)
Mandarin accounts for a significant part of citrus production in Colombia. The use of 1-methylcyclopropene (1-MCP) inhibits the action of ethylene and constitutes a common practice for extending the postharvest life of perishable products. In citrus fruits, especially tangerine var. Arrayana, the effect of 1-MCP in combination with storage temperature has not been characterized. It is therefore important to establish the effect of these two combined factors on the postharvest behavior of mandarin fruits (Citrus reticulata L.) var. Arrayana harvested at commercial maturity. A completely randomized design with a 3 x 2 factorial arrangement was employed for the study: the first factor corresponded to storage temperatures of 6, 12 and 18ºC (room temperature), while the second factor was the presence or absence of 1-MCP (0,5 µL L-1 for two hours). The fruits were kept in storage room for a period of 34 days, during which total soluble solids, respiratory rate, total titratable acidity, firmness, total chlorophyll and color index were assessed every 7 days. After 22 days of storage, and regardless of the application of 1-MCP, 12ºC treatment stimulate fruit skin discoloration and increased chlorophyll degradation and color index. At this temperature, no frost damage occurred and the application of 1-MCP was not important. However, at temperatures below 6ºC, lower degreening and color index values were observed, thus leading to longer shelf life times. According to the results, 12ºC is a suitable temperature for the degreening of tangerine var. Arrayana until 22 days of storage; and 6ºC is an alternative temperature for longer storage times, up to 34 days. No postharvest management had been previously reported for this variety.